Abortion among young adults aged 18 to 25 years, attending Kajjansi Health Centre IV, A Cross-sectional Study. - Nafungo, Mercy; Kibirige , Gordon; Nalubega, Jane Frank; Okello, Elizabeth; Akankwasa, Edith (Student’s Journal of Health Research Africa, 2026)
Background: The rate of abortions in Uganda is concerning, with abortion-related deaths increasing, most especially among young mothers. This study thus focused on investigating the factors associated with increased abortions among young adults aged 18-25 years at Kajjansi Health Centre IV. Methodology: The study employed a cross-sectional design at Kajjansi Health Centre IV for a period of three months, from May 2025 to August 2025. An estimated 114 respondents obtained through simple random sampling participated in the study. Data was collected using a questionnaire, analyzed, and presented in the form of tables, graphs, and pie charts. Results: Findings revealed that the majority of the respondents were single (44.7%) or separated (17.5%), with 59.6% acknowledging that marital status influenced their decision to seek abortion. Educational attainment was relatively high, with 70.2% affirming that education affected their reproductive choices, and 85.1% reporting prior exposure to reproductive education. Despite this, 75.4% had decided to abort, and 75.4% expressed only moderate confidence in that decision. Economic vulnerability was evident, with 74.6% of the respondents identifying as low-income and nearly one-fifth unemployed. While 48.2% cited economic status as a factor in abortion decisions, access to safe abortion services remained moderate, 57.9%, with 13.2% reporting no access at all. Conclusion: Financial insecurity is key in reproductive decision-making, often pushing young adults towards abortion due to the inability to support the child. Whereas unstable relationships significantly contribute to abortion, education is a double-edged factor. Recommendation: These findings highlight the urgent need for targeted interventions that enhance reproductive health education, economic empowerment, and access to safe abortion services within this demographic.